The Effectiveness of Group Investigation (GI) Learning Models and Team Quiz on Learning Outcomes and Cooperation Character on Nervous System Materials - Pramasta, Bagas; Utami, Nur Rahayu; Purwantoyo, Eling (Journal of Biology Education, 2021)
The purpose of this study is to reveal the effectiveness of the Group Investigation and Team Quiz learning models on learning outcomes and the character of cooperation on the material of the nervous system. The Research using Pre-Experimental Design with One Group Pretest Posttest Design.The study population was all students of Class XI IPA SMAN 16 Semarang. The study uses the saturation sampling technique. Research data in the form of cognitive, affective, psychomotor learning outcomes, cooperative character values, activities, student and teacher responses. Cognitive learning results are obtained from classical completeness calculations and N-gain test. The results showed that students' classical completeness was 86.66%. N-gain test results of 100% of students are in the criteria of being medium and high. The value of the character of student cooperation with good and very good criteria is 96.2%. Affective learning outcomes are very good criteria with a value of 87%. Psychomotor learning outcomes are highly skilled criteria with a value of 82.88%. The conclusion of the research is the application of the Group Investigation and Team Quiz Learning Model effectively to the learning outcomes and the character of student cooperation on the nervous system material at SMAN 16 Semarang.